Implementation of experiential learning method in mechanical drawing course to enhance student understanding through real projects - Ridhollah Nasution; Arwizet K; Yolli Fernanda (Journal of Engineering Researcher and Lecturer, 2024)
This research explores the implementation of experiential learning to improve students' understanding and skills in mechanical drawing using CAD software. We used this approach to identify challenges in learning mechanical engineering, including lack of time to learn CAD, suboptimal mechanical drawing skills, and limitations in producing details of mechanical components. Through a quasi-experiment with experimental and control classes, we measured the impact of the experiential learning method on improving conceptual understanding and practical skills in mechanical drawing. The results show that this approach is effective in improving students' understanding of detailed drawings and practical skills. The implementation of Experiential Learning also improved students' cognitive learning outcomes and psychomotor skills in mechanical drawing. The findings highlight the importance of adaptive and technological approaches to engineering education that are aligned with modern industry needs.